Implementasi prosedur pembiayaan gadai emas pada bank syariah di Indonesia - Fajaryati, Suci (Maliki Interdisciplinary Journal, 2023)
Indonesia Islamic bank KCP Bima Kartini is one of the Islamic banks engaged in the financial sector by offering various financing products to help people's needs. One of the financing products managed by Bank Syariah Indonesia KCP Bima Kartini is a gold pawning product. This study aims to find out how to implement gold mortgage financing. The research method used in this study is a qualitative method with a Field Research approach (field research). Field Research is qualitative research, in which a researcher makes observations by directly engaging in small-scale research. The results of this study indicate that the procedure for implementing gold pawning financing, Bank Syariah Indonesia KCP Bima Kartini in practice complies with the provisions of the National Sharia Council of the Indonesian Ulama Council No.25/III/2002 and No.26/III/2002 concerning gold pawning. that all procedures that have been carried out do not violate Islamic law and principles.